High Production Rates Sustain In Vivo Levels of PD-1(high) Simian Immunodeficiency Virus-Specific CD8 T Cells in the Face of Rapid Clearance - Petrovas, Constantinos (American Society for Microbiology, 2013)
Programmed Death 1 (PD-1) expression by human/simian immunodeficiency virus (HIV/SIV)-specific CD8 T cells has been associated with defective cytokine production and reduced in vitro proliferation capacity. However, the cellular mechanisms that sustain PD-1(high) virus-specific CD8 T cell responses during chronic infection are unknown. Here, we show that the PD-1(high) phenotype is associated with accelerated in vivo CD8 T cell turnover in SIV-infected rhesus macaques, especially within the SIV-specific CD8 T cell pool. Mathematical modeling of 5-bromo-2′ deoxyuridine (BrdU) labeling dynamics demonstrated a significantly increased generation rate of PD-1(high) compared to PD-1(low) CD8 T cells in all memory compartments. Simultaneous analysis of Ki67 and BrdU kinetics revealed a complex in vivo turnover profile whereby only a small fraction of PD-1(high) cells, but virtually all PD-1(low) cells, returned to rest after activation. Similar kinetics operated in both chronic and acute SIV infection. Our data suggest that the persistence of PD-1(high) SIV-specific CD8 T cells in chronic infection is maintained in vivo by a mechanism involving high production coupled with a high disappearance rate.